2019
DOI: 10.1103/revmodphys.91.025002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring astrophysics-relevant magnetohydrodynamics with pulsed-power laboratory facilities

Abstract: Laboratory facilities employing high pulsed currents and voltages, and called generally "pulsed-power facilities", allow experimenters to produce a variety of hydrodynamical structures replicating, often in a scalable fashion, a broad range of dynamical astrophysical phenomena. Among these are: astrophysical jets and outflows, astrophysical blast waves, magnetized radiatively dominated flows and, more recently, aspects of simulated accretion disks. The magnetic field thought to play significant role in most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 230 publications
(250 reference statements)
2
40
0
Order By: Relevance
“…When using an external magnetic field for this task, there must be sufficient time for the field to penetrate into and couple to the plasma before the intended interactions of the flow take place [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…When using an external magnetic field for this task, there must be sufficient time for the field to penetrate into and couple to the plasma before the intended interactions of the flow take place [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the similarity of the Mather-type PF geometry to coaxial plasma accelerators (Marshall guns), the mechanism for generating plasma flow is more like the mechanism observed in conical wire arrays (Lebedev et al . 2019). A plasma flow is formed in the pinch region with a diameter of approximately 1 cm and 5–10 cm long.…”
Section: Set-up Of the Experimentsmentioning
confidence: 99%
“…In particular, significant progress was achieved on the MAGPIE facility (Imperial College London, UK). In the series of experiments performed at this facility, the rotation effects detected in protostellar jets were modelled in the laboratory, the interaction of high-speed radiation-cooled jets with the environment were modelled and possible mechanisms of the jet formation have been elucidated among other results (Lebedev, Frank & Ryutov 2019). Interesting results were also obtained on a high-power laser in the LULI laboratory (Ecole Polytechnique, Paris, France), where it was shown that applying a poloidal magnetic field can provide effective collimation of the plasma flow (Albertazzi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Astrophysical jets have been simulated in laboratory experiments using pulsed power technology by Hsu & Bellan (2002), Lebedev et al (2005), You et al (2005), Gourdain & Seyler (2014), and Lavine & You (2019). Experiments simulating astrophysical jets using pulsed power have been reviewed by Lebedev et al (2019), and experimental observations have been reproduced using 3D MHDnumerical codes by Ciardi et al (2007), Huarte-Espinosa et al (2013), and Zhai et al (2014). Li et al (2016) have simulated astrophysical jets in a laboratory experiment that used a high-power laser.…”
Section: Introductionmentioning
confidence: 99%